2010
DOI: 10.1016/j.jaad.2010.02.056
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic nodal evaluation improves prognostic accuracy in Merkel cell carcinoma: Analysis of 5823 cases as the basis of the first consensus staging system

Abstract: Background The management of Merkel cell carcinoma (MCC) has been complicated by a lack of detailed prognostic data and by the presence of conflicting staging systems. Objective To determine the prognostic significance of tumor size, clinical vs pathologic nodal evaluation, and extent of disease at presentation and thereby derive the first consensus staging/prognostic system for MCC. Methods 5,823 prospectively enrolled MCC cases from the National Cancer Data Base (NCDB) had follow-up data (median 64 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
457
3
13

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 498 publications
(506 citation statements)
references
References 23 publications
18
457
3
13
Order By: Relevance
“…In the 70 cases, multivariate Cox regression analysis assessed p63 expression to be a strong independent prognostic factor (Po0.001) followed by disease stage (P ¼ 0.008). Without unduly dismissing the importance of staging, it should be remarked that the real clinical dilemma is related to localised stage I and II Merkel cell carcinomas, which represent the vast majority at first presentation 4 and where no predictor is available to identify the large number of cases behaving aggressively 4 and to plan therapy accordingly. Indeed, we wish to stress that the utility and importance of data from the current study is that p63 expression was found to be strongly associated with a worse prognosis in patients with low-stage Merkel cell carcinoma and represents a new independent marker of clinical evolution in these patients (Po0.0001) (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the 70 cases, multivariate Cox regression analysis assessed p63 expression to be a strong independent prognostic factor (Po0.001) followed by disease stage (P ¼ 0.008). Without unduly dismissing the importance of staging, it should be remarked that the real clinical dilemma is related to localised stage I and II Merkel cell carcinomas, which represent the vast majority at first presentation 4 and where no predictor is available to identify the large number of cases behaving aggressively 4 and to plan therapy accordingly. Indeed, we wish to stress that the utility and importance of data from the current study is that p63 expression was found to be strongly associated with a worse prognosis in patients with low-stage Merkel cell carcinoma and represents a new independent marker of clinical evolution in these patients (Po0.0001) (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…4,11 Pathology samples included resection specimens. Haematoxylin and eosin-stained slides (H&E) were available for all cases.…”
Section: Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors recognized as associated with poor prognosis are size of the tumor and presence of metastases according to the AJCC staging (4,47,55,(64)(65)(66)(67)(68), and immunosuppression (65,69,70). Recently, histological and immunochemistry markers have been described as potentially associated with poor outcome like low tumor infiltrating CD8 + T cells (101) and P53 and P63 expression and gen mutations (54, 68, 74) ( Table 2).…”
Section: Mcpyv Status and MCC Prognosismentioning
confidence: 99%
“…3 There is an overall 5-year survival rate of 40%, with stage being a significant prognosticator. 3,4 Merkel cell polyomavirus was discovered in Merkel cell carcinoma and found to be clonally integrated in B80% of cases. [5][6][7] Merkel cell polyomavirus has a high seroprevalence in the general population and asymptomatic infection begins in childhood.…”
mentioning
confidence: 99%